Mendorong Kreativitas Ekonomi Ikatan Remaja Masjid (IRMAS) Jami’ Darussalam Menganti Kesugihan Cilacap Melalui Pengembangan Usaha Mandiri - Sodikin Sodikin; Risqa Naila Khusna Syarifah; Roni Nur Triwobowo (BADAN PENERBIT STIEPARI PRESS, 2026)
Youth have a strategic role in bringing about positive change, both through social and economic innovation. A potential platform that supports economic empowerment is the mosque youth association (IRMAS). IRMAS Jami’ Darusalam Menganti currently relies solely on TPQ contributions of IDR 10,000/month/student, with no productive economic activities yet. Meanwhile, around the mosque there are chicken noodle and meatball vendors, and the mosque yard has not been utilized other than for parking. IRMAS Jami’ Darusalam Menganti Cilacap has not yet developed independent creative and productive economic skills, lacks sustainable business initiatives to support both the association’s funds and family economy, and has no access to capital to start creative and independent economic activities. The aim of this community service program is to create alternative creative business opportunities through empowering IRMAS to become economically productive. The methods applied include knowledge and skill transfer in hydroponics, digital marketing, and providing alternative solutions for capital access. The results show that IRMAS Jami’ Darusalam gained improved knowledge and skills in creative economy, the establishment of hydroponic farming in the mosque’s backyard, local companies and the village government providing support in capital access, and the utilization of harvested vegetables contributing to the community’s free nutritious meal program.